Novel three-dimensional acellular dermal matrix for prepectoral breast reconstruction: First year in review with BRAXON®Fast - Berna, Giorgio; De Grazia, Alessia; Antoniazzi, Elisa; Romeo, Marco; Dell’Antonia, Francesco; Lovero, Stefano; Marchica, Paolo; Rizzetto, Christian; Burelli, Paolo (Frontiers in Surgery, 2022)
Implant-based breast reconstruction is part of breast cancer treatment, and increasingly optimized reconstructive procedures exploit highly biocompatible materials to ensure enhanced aesthetic-functional results. Acellular dermal matrices (ADMs) are collagen-based materials that made prepectoral implant placement possible, thanks to their bioactive antifibrosis action. Recently, the first three-dimensional ADM, BRAXON®Fast, has been produced. Its 3D design represents the technological evolution of BRAXON® ADM, a flat collagen matrix, and allows for a time-saving complete wrapping of the synthetic prosthesis, thus creating a total biological interface on the implant with patient's tissues. Here, we report our experience on the first 23 eligible patients who received BRAXON®Fast-assisted prepectoral reconstruction. On a total of 27 breasts, the overall complication rate was 11.1%, including one minor seroma (3.7%), one case of necrosis (3.7%), and one implant removal due to infection. As new-generation devices, 3D ADMs showed an effective performance, allowing to reduce the overall exposure time for implant preparation and providing an optimal safety profile.